2010
DOI: 10.1159/000319072
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Inflammation and Cytotoxicity by Dipyridamole in Brain Endothelial Cells

Abstract: Background: Increasing evidence suggests that beyond its antiplatelet properties, dipyridamole may have pleiotropic effects on other cells within the neurovascular elements of the brain. In this experimental cellular study, we asked whether dipyridamole can ameliorate brain endothelial injury after exposure to inflammatory and metabolic insults. Methods: Human brain endothelial cells were grown in culture, and exposed to TNFα (continuously for 20 h) or subjected to oxygen-glucose deprivation (OGD; 6 h of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 71 publications
(49 reference statements)
1
35
0
Order By: Relevance
“…Begandt et al reported that DPA increased gap junction coupling of bovine aortic ECs [48], which resulted in better blood flow and increased vascular motility [49,50]. Guo et al [51] found that DPA reduced brain EC death after injury from oxygen–glucose deprivation by reperfusion. On the basis of the above reports, it is convincing that DPA would promote vascular endothelial cell growth, which is consistent with our observation in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Begandt et al reported that DPA increased gap junction coupling of bovine aortic ECs [48], which resulted in better blood flow and increased vascular motility [49,50]. Guo et al [51] found that DPA reduced brain EC death after injury from oxygen–glucose deprivation by reperfusion. On the basis of the above reports, it is convincing that DPA would promote vascular endothelial cell growth, which is consistent with our observation in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Other features of dipyridamole further support its potential utility in MS, and, because it is already in long-term use for stroke prevention, its potential chronic use in patients with MS has a clinical precedent. Dipyridamole also has antioxidant effects [39], and it inhibits the expression of matrix metalloproteinase 9 (MMP-9) [40,41]. These molecules are thought to contribute to MS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They were seeded at a density of 1 × 10 5 cells per well onto 12-well culture plates, and incubated in EBM-2 medium with endothelial growth supplements (Lonza, Walkersville, MD, USA) at 37°C in 5% CO 2 until they reached 70% confluence. To investigate the effects of PGRN on the TNF-α induced inflammation model, the culture medium was removed, and cells were washed twice with PBS, before they were treated with varying concentrations of recombinant human PGRN (rh-PGRN; Recombinant Human Progranulin; R&D Systems, Inc.), and 10 ng/mL of TNF-α (Recombinant Human TNF-α; R&D Systems, Inc.) for 20 h, in accordance with the methods described previously [24]. Following these treatments, cell lysates were collected, and Western blot analysis was performed in order to assess the expression levels of intercellular adhesion molecule-1 (ICAM-1), using the protocol described above, and the primary antibodies of rabbit anti-ICAM-1 (1:1,000; Cell Signaling Technology) and mouse anti-β-actin (1:5,000; Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%